Impact Of Burnout And Work Life Balance On Job Satisfaction Of Tabing SPBU Employees, Padang - Amelia Novita Sari; Ash Shadiq Egim (CAKRAWALA : Management Science Journal, 2024)
This research aims to see the effect of (1) Burnout on job satisfaction of Tabing gas station employees. (2) Work life balance on job satisfaction of Tabing gas station employees (3) Burnout and work life balance together on job satisfaction of Tabing gas station employees. This research uses a quantitative research method, where the sampling technique uses a total sampling technique, with a total sample of 36 Tabing gas station employees. The analysis technique is multiple regression analysis. The results of this research show that (1) Burnout does not have a significant effect on job satisfaction of Tabing gas station employees. (2) Work life balance has a significant effect on job satisfaction of Tabing gas station employees. (3) Burnout and work life balance together influence the job satisfaction of Tabing gas station employees.